Rayford Whittingham Logan papers - Logan, Rayford Whittingham, 1897-1982.
Correspondence, diaries, and biographical material documenting Logan's concern with racial inequality and his career as an historian of Africans and African Americans. Topics include his army service in France during World War I; the Pan-African movement of the 1920s and 1930s; Haitian diplomatic soirées; the founding conference of the United Nations, San Francisco, Calif. (1945); Logan's meetings with African independence leaders, Kwame Nkrumah and Nnamdi Azikiwe; colleagues including Mordecai W. Johnson; and his career at Howard University. Correspondents include Harry T. Burleigh, Betty Riis, Roger William Riis, and Logan's wife, Ruth Robinson Logan.
Microfilm edition of diary, 1943-1944, available
Microfilm produced from originals in the Manuscript Division.
Historian and educator; died 1982.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Azikiwe, Nnamdi, -- 1904-1996.; Burleigh, H. T. -- 1866-1949 -- Correspondence; Johnson, Mordecai W. -- 1890-1976.; Logan, Ruth Robinson -- Correspondence; Nkrumah, Kwame, -- 1909-1972.; Riis, Betty -- Correspondence; Riis, Roger William, -- 1894- -- Correspondence; Howard University -- Faculty; Africans; African American universities and colleges; African Americans; Diplomatic and consular service, Haitian -- United States; Equality; Pan-Africanism.; Race discrimination; Universities and colleges -- Washington (D.C.); World War, 1914-1918 -- France; Africa -- History -- Autonomy and independence movements; Haiti -- Social life and customs; Educators; Historians